Indigenous Ethics and Bionomic Concepts in the New Latin American Constitutions and their Contribution to the Environmental Debate - da Rosa, Ronei Alberti (Revista Ágora Filosófica, 2016)
In Latin America, the public sphere has historically conceded a narrow participation range to the indigenous people. Following democratization that changed the continent starting in the 1980s, some Andean countries began to adopt constitutional reforms that enabled the indigenous communities to participate in national decision making.   They even went to the point of putting the traditional justice applied by minority groups and the national modern constitutions on the same level.  This is particularly the case with Ecuador and Bolivia. In 2008, Ecuador became the first nation to codify and include in its constitution the Rights of Nature. The Ecuadorian ecosystem, thus, became a person of rights, possessing inalienable rights to exist and flourish. Citizens were as well given authority to petition on behalf of the ecosystem. In Bolivia, the New State Politic Constitution, approved in 2009, bestows upon the indigenous groups the right of applying their own justice. This process expresses the accommodation of two juristic zones: that from the Enlightenment positivistic tradition and the autochthonous one. This new legal architecture included regional popular ethical principles that widened the debate about the natural environment and the way the state deals with it. It is the case of concepts like Pachamama (a holistic notion of world) and sumak kawsay (equivalent to that of wellbeing, or even the Good Life). Their revival has diversified the internal juridical landscape by adding an Amerindian perspectivism. This paper will investigate the range of the application of indigenous Ethics and bionomic concepts in multicultural societies, specifically in the case of Latin American countries that have included such elements in their constitutions. It will discuss whether that sort of parallel axiological system could represent a valuable contribution to the global environmental debate.